Analysing neutron radiation damage in YBa2Cu3O7–x high-temperature superconductor tapes - Linden, Y; Iliffe, WR; He, G; Danaie, M; Fischer, DX; Eisterer, M; Speller, SC; Grovenor, CRM (Wiley, 2022)
Superconducting windings will be necessary in future fusion reactors to generate the strong magnetic fields needed to confine the plasma, and these superconducting materials will inevitably be exposed to neutron damage. It is known that this exposure results in the creation of isolated damage cascades, but the presence of these defects alone is not sufficient to explain the degradation of macroscopic superconducting properties and a quantitative method is needed to assess the subtle lattice damage in between the clusters.